Enhanced recovery after surgery or fast-track surgery and the perioperative period of acute gastrointestinal perforation: a systematic review and meta-analysis - Wang, Chuan; Qiu, Wenna; Qu, Hailong; Li, Pengfei; Xu, Wei; Fang, Yanwei (Frontiers in Surgery, 2025)
BackgroundReports of an association between enhanced recovery after surgery (ERAS) or fast-track surgery (FTS) and the perioperative period of acute gastrointestinal perforation are inconsistent. Therefore, we systematically evaluate the safety and efficacy of ERAS or FTS in the perioperative of acute gastrointestinal perforation.MethodsRandomized controlled trial (RCT) or controlled clinical trial (CCT) on the application of ERAS/FTS in the perioperative management of acute gastrointestinal perforation was conducted by PubMed, Medline, Web of Science, Ovid, Elsevier ScienceDirect, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Database (CBM), Wanfang Data, and WHIP. The methodology quality and data extraction were evaluated by two researchers, and meta-analysis was performed by Stata 11 software.ResultsA total of 20 RCTs and 7 CCTs were included in the study, involving 1,864 patients—917 in the ERAS/FTS group and 947 in the control group. The results of the meta-analysis showed that the stress response CRP and complication rate of the ERAS/FTS group were significantly lower than those of the traditional treatment group, the time of first out-of-bed activity and the time of postoperative first exhaust and eating were advanced, and the cost and the length of hospital stay were decreased (p < 0.05). Egger's test showed no publication bias (p > 0.1). However, only two and three studies mentioned operative time and pain management, respectively, so the meta-analysis could not be performed.ConclusionThe application of ERAS/FTS in perioperative management of acute gastrointestinal perforation is safe and effective.